Improving Code Response Time through Strategic Positioning of Nursing House Supervisors: Results of a Nurse-Led Intervention - Noah R. Zanville; Paula T. Smith; Albis A. Aguiar; Joan Simon-Smith; Jessenia Menendez; Alice J. Cockerel; Rosalina P. Butao; Marguerite Rowell (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2020)
Background: In many settings, the nursing house supervisors (NHS) are a critical part of the entity's code response team. To date, much of the research on code response has focused on improving response times through staff-focused interventions such as simulation training. However, use of data to determine where to physically place NHS in the building to optimize code response times has received little attention, especially in an outpatient oncology setting. Purpose: To test whether using data on code frequency/location to strategically position NHS could reduce mean code response times in large (450,000-ft2) outpatient cancer center. Methods: Data on code volume, type, distance and estimated response time before and after strategic repositioning was collected by staff over a 238-day period occurring between September, 2019 and April, 2020. Results: Over an eight-month period, NHS staff responded to 64 codes. Prior to repositioning, 77.3% of codes required NHS to travel to a different building and through at least one floor and/or departments to arrive at the code. After strategic repositioning, mean code response times at our center fell from 3.4±0.7 min, on average, to 1.5 ± 0.6 min (p < .000). Improvements in code response times and distance travelled were observed regardless of code type, time of day, or individual NHS responding to the code. Conclusions: Results suggest that a data-driven strategy for determining where to place NHS in the building based on code frequency and location may be a useful way for oncology centers to improve code response times.